2011
DOI: 10.12968/ijpn.2011.17.4.177
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on spiritual care at Hospice Africa Uganda

Abstract: Although the palliative care workers at HAU have views on spirituality and spiritual care that have much in common with the palliative care literature from North America and Europe, they also face more specific challenges. These include providing spiritual care in a resource-poor setting to patients undergoing severe economic hardship, and providing spiritual care to those with traditional African religious beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 11 publications
0
43
0
2
Order By: Relevance
“…Both ‘feeling at peace’ and ‘feeling life is worthwhile’ were interpreted in terms of patients’ perception of life and the world and relationships to others. A recent study in Uganda found that hospice staff also had a relational understanding of patients’ spiritual well-being in terms of interconnectedness and a person’s relationship to their culture, society, neighbours and family [43]. The influence of social relationships on spiritual well-being reflects the collectivism of African culture and the principle of Ubuntu , which appears in many African languages and expresses the view that the essence of being human is interconnectedness and one cannot exist as a human being in isolation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Both ‘feeling at peace’ and ‘feeling life is worthwhile’ were interpreted in terms of patients’ perception of life and the world and relationships to others. A recent study in Uganda found that hospice staff also had a relational understanding of patients’ spiritual well-being in terms of interconnectedness and a person’s relationship to their culture, society, neighbours and family [43]. The influence of social relationships on spiritual well-being reflects the collectivism of African culture and the principle of Ubuntu , which appears in many African languages and expresses the view that the essence of being human is interconnectedness and one cannot exist as a human being in isolation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reflected the experience of physicians: one focused on residents in family medicine [49], and the other focused on palliative care physicians [50]. Four addressed interdisciplinary care teams: palliative care staff [51,52], medical directors and chaplains [53], multifaceted organizational perspective (nurses, patients, family, chaplains, and hospital administrators) [54]. One study focused both on nurses' educational outcomes from a training session, as well as patient outcomes [55].…”
Section: Key Pointsmentioning
confidence: 99%
“…[2][3][4][5] The traditional position of sub-Saharan West-African communities toward death and dead bodies can be summed up as follows. [6][7][8][9][10] There are three parts in Man: the body, in decomposition then putrefaction after death; the spirit, that stays on Earth (with deification by relics, for example); and the soul, that comes back to God (or the Gods). Death is thus a kind of birth in another world, as birth is a kind of death in another world.…”
Section: Discussionmentioning
confidence: 99%